2011
DOI: 10.1186/1471-2199-12-10
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and functional characterization of the murine Smoothelin-like 1 promoter

Abstract: BackgroundSmoothelin-like 1 (SMTNL1, also known as CHASM) plays a role in promoting relaxation as well as adaptive responses to exercise, pregnancy and sexual development in smooth and skeletal muscle. Investigations of Smtnl1 transcriptional regulation are still lacking. Thus, in this study, we identify and characterize key regulatory elements of the mouse Smtnl1 gene.ResultsWe mapped the key regulatory elements of the Smtnl1 promoter region: the transcriptional start site (TSS) lays -44 bp from the translati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…CSRP3 and SYNPO2 translocate from the cytoplasm to the nucleus in response to physical stretch, stress or strain where they impact gene transcription and myogenesis through interactions with transcription factors such as MyoD [ 36 , 37 ]. The second most highly DEP, SMTNL1, also undergoes nuclear translocation with strong impacts on gene transcription [ 38 , 39 ]. The integral role that these proteins have in gene transcription could indicate a potential disruption in adaptive responses to muscle strain or stress in MFM.…”
Section: Discussionmentioning
confidence: 99%
“…CSRP3 and SYNPO2 translocate from the cytoplasm to the nucleus in response to physical stretch, stress or strain where they impact gene transcription and myogenesis through interactions with transcription factors such as MyoD [ 36 , 37 ]. The second most highly DEP, SMTNL1, also undergoes nuclear translocation with strong impacts on gene transcription [ 38 , 39 ]. The integral role that these proteins have in gene transcription could indicate a potential disruption in adaptive responses to muscle strain or stress in MFM.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggested that SMTNL1 may function as a transcriptional regulator of MYPT1 expression in smooth and striated muscle, altering their contractile properties. This putative role is supported by nuclear localization of SMTNL1 upon phosphorylation at Ser-301 in response to cAMP/cGMP and by the presence of a number of regulatory transcription factor binding sites in the promoter region of Smtnl1 (11,13). SMTNL1 also shows sex-related differences in expression and function, in that male mice have a 2-fold increase in levels compared with females, and exercise-adapted muscle tissues from smtnl1 Ϫ/Ϫ female mice respond differently to adrenergic agonists (11,12).…”
Section: Smtnl1 Is a Bifunctional Co-regulator Of Pr-b Signaling And mentioning
confidence: 91%
“…This suggests that SMTNL1 is a bifunctional co-regulator of PR-B signaling and thus provides a molecular mechanism whereby PR-B is targeted to alter gene expression patterns to coordinately promote alterations in uterine smooth muscle function during pregnancy (12). Based on these observations we have speculated that SMTNL1 could function as a transcriptional regulator of SKM differentiation and plasticity; this putative role is evident by the nuclear localization of the protein upon phosphorylation at serine 301 by protein kinase G/A and by the presence of a number of regulatory transcription factor binding sites in the promoter region of smtnl1 (13). In this study we show that pregnancy induces switching of SKM to a glycolytic phenotype and this effect is mediated through SMTNL1.…”
mentioning
confidence: 99%